1995
DOI: 10.1093/infdis/172.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Effects of Ivermectin on Adult Parasites in Onchocerciasis Patients in the Onchocerciasis Control Programme in West Africa

Abstract: Ivermectin is an effective drug for the treatment of human onchocerciasis, a disease caused by the parasitic filarial nematode Onchocerca volvulus. When humans are treated, the microfilariae normally found in the skin are rapidly and very nearly completely eliminated. Nonetheless, after a delay, microfilariae gradually reappear in the skin. This study is concerned with the causes of this delay. Hypotheses are tested by comparing the results of model calculations with skin microfilaria counts collected from 114… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 18 publications
4
100
1
1
Order By: Relevance
“…Although their modelling approach is different from ours, and the frequency of treatment in Asubende, Ghana (Alley et al 1994) was annual rather than 6-monthly as in Guatemala, the results of both studies are compatible and also comparable to those obtained by Basáñ ez et al (2008), who modelled the effect of a single ivermectin dose. However, Plaisier et al (1995) found that a progressive reduction of microfilarial production with each dose would be the scenario most consistent with the data. It would be very interesting to reanalyse such data with the modelling approach presented here, as projections of onchocerciasis elimination assume operation of such cumulative effects (Winnen et al 2002).…”
Section: Concluding Remarks and Future Directionssupporting
confidence: 77%
See 2 more Smart Citations
“…Although their modelling approach is different from ours, and the frequency of treatment in Asubende, Ghana (Alley et al 1994) was annual rather than 6-monthly as in Guatemala, the results of both studies are compatible and also comparable to those obtained by Basáñ ez et al (2008), who modelled the effect of a single ivermectin dose. However, Plaisier et al (1995) found that a progressive reduction of microfilarial production with each dose would be the scenario most consistent with the data. It would be very interesting to reanalyse such data with the modelling approach presented here, as projections of onchocerciasis elimination assume operation of such cumulative effects (Winnen et al 2002).…”
Section: Concluding Remarks and Future Directionssupporting
confidence: 77%
“…45) were releasing live microfilariae. This finding is less easy to compare to our result although the two may be consistent if ivermectin eliminates microfilarial production in a proportion of worms and has little or no effect in the remaining worms, as proposed by Plaisier et al (1995).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…1B, Table 1). Transmission intensity was concomitantly measured only in the Guatemalan study (18), so it is difficult to ascertain whether this is due to a reduction in the force of infection or a cumulative impact of ivermectin on female worm fertility (13,14). No significant difference in the rate of skin repopulation was seen between rounds 1, 2, and 4 if hosts with no detectable microfilariae at the time of treatment were excluded from the analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ivermectin has a limited effect on the viability of O. volvulus microfilaria, [91][92][93][94][95] which have an estimated reproductive life span of 12-15 years. [96][97] Consequently single treatments with ivermectin do not change the infection status of treated subjects, and the effect of ivermectin mass treatment on infection prevalence is primarily due to reduction in transmission. [98][99][100][101][102][103] Between 1987 and 2011, the Mectizan Donation programme approved 139,265,010 ivermectin treatments for Africa.…”
Section: Parasitesmentioning
confidence: 99%